STUDENTS’ ABILITIES TO SOLVE MATHEMATICAL PROBLEMS ACCORDING TO ACCREDITATION LEVELS - Mairing, Jackson Pasini (International Journal of Education, 2017)
Problem solving is important for mathematical learning because it enables students to enhance high thinking skills and positive attitudes. This research aimed at describing and comparing the abilities of junior high school students in grade VIII from one of the regencies/cities in Central Kalimantan (Indonesia) in solving mathematical problems based on schools’ accreditations (A, B, C, and unaccredited), and schools’ status (public and private). The researcher gave three mathematical problems to the students from 20 samples of schools. The schools were randomly selected from the population consisting of 62 junior high schools. Each student’s solution was scored using a holistic rubric. The scores were summarized using some statistics represented in tables and graphics and were analyzed using a Kruskal-Wallis nonparametric test because the data were not normally distributed. The finding indicated that the average scores of the public and private schools’ students were 4.71 and 3.49 (scale 0-12), respectively. Based on the percentages, namely 1.91% and 39.66%, the students were classified as good and naive problem solvers, respectively. Further test revealed that the students from the A-accredited public schools significantly achieved the highest score for problem solving skills. Meanwhile, the students in the A-accredited and the unaccredited private schools did not show a significant difference in the skills. Similar result was also found in the public schools which were accredited B and C, and unaccredited.